Liberalism from the Perspective of Islamic Education and Its Implications for the National Education System - Shafika Fadillah; Sondos Jehad Shnewra; Mariam Elbanna (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study aims to analyze the influence of liberalism principles from the perspective of Islamic education and its implications on the national education system in Indonesia. Theoretical framework: The theoretical framework used is the principle of liberalism, which emphasizes individual freedom and critical thinking in education. Liberalism is considered to offer a unique perspective to build an education system in a plural and democratic society. Literature review: The literature review includes an analysis of liberalism educational theories, national education policies, and scientific literature related to the application of liberalism values in education. This study explores the benefits, challenges, and relevance of the principles of liberalism in the context of the education system in Indonesia. Methods: The research uses a qualitative method with a literature study approach. The data was analyzed through the study of various scientific literature, educational policies, and educational theories related to the principles of liberalism. Results: The results of the study show that the application of liberalism principles in the education system can, increase students' freedom of thought, creativity, and critical ability, and help students face the challenges of globalization. However, there are challenges such as Incompatibility with local cultural values, and the need to adjust the curriculum to be relevant to the Indonesian context. Implications: This research suggests the need for an adaptive education policy, which can: Integrate freedom of thought and independence in learning and maintain national identity and local cultural values, This approach is expected to create an inclusive, relevant, and balanced education system. Novelty: The novelty of this research lies in the analysis of the balance between the values of freedom in liberalism and traditional social norms in the context of national education. This research provides new insights into how liberalism can be applied without neglecting local cultural roots.